(3ejRGf GdCLSGOs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3cJGH ejRGf GdCLSGO bGd ajg HYO cdGe Whjd(B: (3GYde Cf ehGRjf Gdce hGdcja s
(3BNQgG (B:s
(3aGLJgO ai eYQaI GdCUhd hYOd GdCQcGf ajchf dc TCf hCi TCf hdjcf gPG GdcdGe BNQ GdebGdI GdSGHbI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B240 - (3U(B249s
(3GdehLhO HYV aUhd efgs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
Keywords: (3GdcjejGA h GdWHjYjGJs